A taxonomic study of the Dryininae (Hymenoptera: Dryinidae) of Japan, with description of a new species of Pseudodryinus - Mita, Toshiharu (Zootaxa, 2009)
The Japanese Dryinidae were studied and 11 species recognized. The following 10 species were recorded for the first time from Japan: Thaumatodryinus alienus Olmi, Dryinus bellicus Olmi, D. chenae Xu, Olmi & He, D. browni Ashmead, D. expolitus Xu, Olmi & He, D. indicus (Kieffer), D. krombeini Ponomarenko, D. pyrillae (Kieffer), D. pyrillivorus Olmi, and D. sinicus Olmi. Pseudodryinus shihoae, new species, is described from Honshu. Thaumatodryinus alienus and D. indicus were reared for the first time from Geisha distinctissima (Walker).